Analisis Penggunaan Aplikasi Tata Kelola BBM : Sebuah Pendekatan Multimetode - Dewi, Lilis Dewi Nurjanah; Nurhanah, Lilis Dewi; Akbar, Gugun Geusan (Sawala : Jurnal Administrasi Negara, 2023)
This study aims to analyze the use of the My Pertamina application using a combined method between TAM (Theory Acceptance Model) and TRA (Theory of Reasoned Action). My Pertamina application is a mobile application developed by Pertamina which is used to provide non-cash fuel oil payment services. The TAM and TRA methods are used as the theoretical framework in this study to understand the factors that influence the acceptance and use of the My Pertamina application by users. TAM acceptance theory focuses on factors that influence users' attitudes toward technology adoption, while TRA addresses factors that influence users' intention to use a system. This research uses a quantitative approach by surveying users of the My Pertamina application. The data collected included users' perceptions of perceived usefulness, perceived ease of use, benefits obtained, perceived subjective norms, and attitudes toward using the application. Data analysis was conducted using regression techniques to test the relationship between the variables in the TAM and TRA models.